A Survey Regarding the Practice of Aural Rehabilitation Among Audiologists in Malaysia - Asyah Hafiza, Mohamad Nor Anual (Universiti Sains Malaysia, 2009)
Aural Rehabilitation (AR) is an important component in audiology. AR helps sufferers with hearing impairment to address the impact of hearing loss, such as communication problems. Audiologists should practise AR activities regularly to lessen the difficulties faced by the patients. This survey aimed to determine the status of AR practice among audiologists working in different settings in Malaysia. Questionnaires were given to 97 audiologists throughout Malaysia by mail. They were asked to fill in the questionnaire and returned it to the researcher using the provided envelope with stamp and address. Only 49 of them (50.5%) responded and this was considered sufficient. Data were analyzed from all 49 respondents. From the study, 93.9 % of the respondents claimed that they practise AR activities on their patients. Out of93.9% audiologists who practise AR activities, 100% of them worked in private hospitals, government hospitals, university hospital and hearing aid centers. While, 57.1% of respondents who worked at university clinic performed AR activities, the remaining 42.9% did not perform AR activities. Only 24.5% of the respondents claimed that they always conduct AR activities during clinical session. Majority of the respondents (91.8%) provided hearing aid orientation services as part of AR activities and 61.2% of them claimed that they do auditory training. In general, AR pmctice in Malaysia seems to be adequate, at least in this study. However, a major concern is that only 24.5% of Malaysian audiologist claimed that they always perform AR activities. This number should be improved as time goes by. Respondents also claimed that the lack of facilities and support, time, exposure and experience are the reasons for not providing effective AR services. Most of them did agree that having more training or seminar in the area of AR can be beneficial to them and the society.